2019
DOI: 10.23922/jarc.2019-009
|View full text |Cite
|
Sign up to set email alerts
|

Current status of colonic stent for obstructive colorectal cancer in Japan; a review of the literature

Abstract: Colorectal cancer is the most common cancer in Japan. Approximately 10%-20% of the patients with colorectal cancer present with large bowel obstruction, and those who present with malignant colonic obstruction (MCO) require urgent decompression because MCO can cause electrolytic fluid imbalance, colonic necrosis, bacterial translocation, and death. Placement of colonic stents (self-expandable metallic stents) for MCO is a major and standard endoscopic treatment that has been available since 2012 in Japan. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 40 publications
4
57
0
1
Order By: Relevance
“…Almost all of the emergency admissions for CRC patients during the observation periods were due to a bowel obstruction which required decompression procedures. The reported incidence of obstructive CRCs requiring decompression procedures is 10%–20% [ 19 , 20 ], which is compatible with the incidence of CRCs with complete obstruction before the state of emergency in our present investigation. However, we observed that the incidence of obstructive CRCs requiring decompression significantly increased to 39% during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Almost all of the emergency admissions for CRC patients during the observation periods were due to a bowel obstruction which required decompression procedures. The reported incidence of obstructive CRCs requiring decompression procedures is 10%–20% [ 19 , 20 ], which is compatible with the incidence of CRCs with complete obstruction before the state of emergency in our present investigation. However, we observed that the incidence of obstructive CRCs requiring decompression significantly increased to 39% during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…The clinical advantages of SEMS insertion in the management of ACO combined with the little negative oncological consequences makes stent a effective clinical method [4] . The limitation of the use of SEMS is the high perforation rate in several randomised controlled trials [24,33,34] , other complications, technical and clinical success rate need to improve for some units, long term exposure under X-ray environmental threats health to operators, especially young doctor [1] et al The variation in the rates of success of SEMS insertion and associated complications reported in the literature suggests that individual expertise institutional experience and available resources [26] has a signi cant bearing on the clinical application of SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…These remaining patients with ACO were included in this study. The signs of obstruction were de ned as (1) distended proximal bowel, liquid surface, transitional zone or collapsed distal bowel on abdominal CT scans ( Fig. 1), which can also demonstrate the level of obstruction position and length of the stricture; or (2) in the colonoscopic evaluation, it is impossible to pass through the stenotic area.…”
Section: Treatment Strategymentioning
confidence: 99%
“…The CROSS system was developed in 2012 by the Japan Colonic Stent Safe Procedure Research Group as a generally applicable technique for the assessment of colonic obstruction and stenosis; the CROSS system is published on the Research Group's home page (http://colon-stent.com/: Table 1). The colonic stents used in BTS for patients with CROSS scores between 0 and 1, and those used for palliative reasons in patients with scores between 0 and 3 are indicated appropriately [15]. At our institute, the indications for stent placement in each case of obstructive colorectal cancer were nally decided based on the CROSS scores, but the decisions were made not by surgeons but by gastroenterologists.…”
Section: Methodsmentioning
confidence: 99%